Medication Adherence Analysis of Type 2 Diabetes Mellitus Patients - Andarmoyo, Sulistyo; Yusoff, Harmy bin Mohamed; bin Abdullah, Berhanudin; Yusop, Yuzana binti Mohd (South East Asia Nursing Research, 2019)
Adherence has an important role in therapy management in patients with type 2 Diabetes Mellitus. This research is to identify and analyze factors related to medication adherence. The design used in this study was a descriptive-analytic design with a cross-sectional approach. The population is type 2 Diabetes Mellitus sufferers of Prolanis Group in Primary Health Care Facilities in the Ponorogo Regency. A sample of 180 respondents was taken by purposive sampling technique. Variable X includes age, gender, education, occupation, income, and length of suffering. Variable Y was medication compliance with type 2 Diabetes Mellitus patients. Data collection used a Morisky Medication Adherence (MMAS-8) questionnaire and was analyzed using the Chi-Square test with a significant level of α <0.05. From the results of the study, it was found that the factors of age, sex, education, employment, income and duration of suffering had a significant relationship with medication adherence for patients with type 2 diabetes mellitus. It is expected that health services develop family and community-based service management. Researchers are further advised to develop programs to improve medication adherence.